2017
DOI: 10.1242/jeb.154419
|View full text |Cite
|
Sign up to set email alerts
|

Prior social experience affects the behavioral and neural responses to acute alcohol in juvenile crayfish

Abstract: The effects of alcohol on society can be devastating, both as an immediate consequence of acute intoxication and as a powerful drug of abuse. However, the neurocellular mechanisms of alcohol intoxication are still elusive, partly because of the complex interactions between alcohol and nervous system function. We found that juvenile crayfish are behaviorally sensitive to acute alcohol exposure and progress through stages that are strikingly similar to those of most other intoxicated organisms. Most surprisingly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 44 publications
2
25
0
Order By: Relevance
“…Since our previous work had shown that the crayfish LG neurons become modestly sensitized after repeated sensory stimulation in normal crayfish saline ( Swierzbinski et al, 2017 ), we first tested the effect of repeated stimulation on MG neuron excitability. After 10 min of baseline recordings, preparations ( N = 5; 3.6 ± 0.16 cm) were perfused for 90 min with fresh crayfish saline and the antenna II nerve was stimulated every 90 s. We observed minor fluctuations in PSP amplitudes in both early and late PSP components throughout this time period ( Figure 2B ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Since our previous work had shown that the crayfish LG neurons become modestly sensitized after repeated sensory stimulation in normal crayfish saline ( Swierzbinski et al, 2017 ), we first tested the effect of repeated stimulation on MG neuron excitability. After 10 min of baseline recordings, preparations ( N = 5; 3.6 ± 0.16 cm) were perfused for 90 min with fresh crayfish saline and the antenna II nerve was stimulated every 90 s. We observed minor fluctuations in PSP amplitudes in both early and late PSP components throughout this time period ( Figure 2B ).…”
Section: Resultsmentioning
confidence: 99%
“…Previous results from our lab demonstrated that juvenile crayfish are behaviorally and physiologically sensitive to EtOH and that this sensitivity is affected by recent social experience ( Swierzbinski et al, 2017 ). When placed in a water-filled tank that contained various concentrations of EtOH, crayfish became more intoxicated over time in a dose-dependent manner, and they progressed through distinct stages of behavioral change.…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations